Impact of Entrepreneurship Program and Individual Orientation on Entrepreneurial Intention: Motivation as Mediator - Dafa Rafif Pratama; Rr Erlina; Nurul Husna (International Forum of Researchers and Lecturers, 2025)
The relationship between entrepreneurship programs, individual entrepreneurial orien-tation, and entrepreneurial intention can be strengthened by entrepreneurial motivation, which acts as an internal drive encouraging individuals to take action toward starting a business. Motivated individuals tend to explore ideas and identify market opportunities to build inde-pendent ventures. Universities play a crucial role by organizing programs that inspire students to pursue self-reliance through entrepreneurship, while also equipping them with relevant knowledge and practical experience to enhance their skills and risk-taking ability. At Univer-sitas Lampung (UNILA), these efforts are facilitated by the Center for Career and Entre-preneurship Development (CCED), which supports various entrepreneurship initiatives aimed at increasing students' motivation and providing hands-on experiences. These experiences strengthen students’ drive to start a business, as entrepreneurial intention is influenced by internal factors such as motivation, reinforced through direct program involvement. Hence, motivation can serve as a mediating variable that links entrepreneurship programs and indi-vidual entrepreneurial orientation with entrepreneurial intention.